Measurements of CO2 and CH4 concentrations in air in a polar ice core - Nakazawa, Takakiyo; Machida, Toshinobu; Esumi, Kenji; Tanaka, Masayuki; Fujii, Yoshiyuki; Aoki, Shuhji; Watanabe, Okitsugu (Journal of Glaciology, 1993)
Abstract Dry and wet air-extraction systems and precise analysis systems of the CO 2 and CH 4 concentrations for a polar ice core were developed to reconstruct their ancient levels. A dry-extraction system was capable of crushing an ice sample of 1000 g into fine powder within 2 min, and its air-extraction efficiency was found to be 98%. The CO 2 and CH 4 concentrations of extracted air were determined using gas chromatography with a flame-ionized detector. The overall precision of our measurements, including air extraction, was estimated to be better than ± 1 ppmv for CO 2 and + 10 ppbv for CH 4 . Preliminary analysis of the ice core drilled at Mizuho Station, Antarctica, showed that the CO 2 and CH 4 concentrations at 3340–3700 year BP were about 280 ppmv and 700ppbv, respectively. The Yamato core drilled at the terminus of the glacial flow near the Yamato Mountains, Antarctica, yielded concentrations of 230–240 ppmv for CO 2 and 520–550 ppbv for CH 4 , suggesting that the core had formed during the glacial period.